Módulo de software para el control del inventario de insumos médicos del Hospital Docente Veterinario “César Augusto Guerrero”. - Jaramillo Jumbo, Danny Michael (2023)
Currently the Directorate of Information Technologies (DTI) of the National University of Loja, focuses on the automation of the different processes that are carried out within the institution, in order to provide information management in an adequate, secure manner. and reliable, which allows optimizing both financial and time resources. Based on this, the objective of this Titration Work (TT, for its acronym) is the development of a software module for the control of the Inventory of Medical Supplies of the Veterinary Teaching Hospital "César Augusto Guerrero", with the purpose of responding to the research question: How does the development of a control module for the Inventory of Medical Supplies based on software for the "César Augusto Guerrero" Veterinary Teaching Hospital influence the interested parties? This TT consisted of three phases, in the first phase, the BPM RAD methodology was applied with the purpose of determining the control process of the Inventory of the Veterinary Teaching Hospital "César Augusto Guerrero" with the BPMN notation, which allowed to represent in a diagram the current process and also a second diagram that represents a proposal for the automation of the inventory control process. For the development of the second phase, the XP methodology was used, the 4+1 model together with the development technologies required by the DTI, thus building a functional software module for inventory control, to later test it in an environment checked. Finally, in the third phase, a test plan was developed in which the set of tests to which the software would be subjected in the controlled environment in which they would be executed was established. In this way, it was possible to answer the research question, corroborating that the software module positively influences the control of the inventory of medical supplies of the Veterinary Teaching Hospital "César Augusto Guerrero", since it meets the needs expressed by the involved, in addition to speeding up the inventory control process, managing to reduce economic and time resources. Next, it is expressed in the future works, based on the TT developed, some improvements to take into account, such as the development of a mobile application as a use option, in addition to the development of a module for inventory adjustment which will allow capture any error entered by the user, all in order to improve the management of processes at the Universidad Nacional de Loja. Keywords: Automation, inventory control, medical supplies, software, BPMN, BPM RAD, XP methodology.